PENGARUH PENGAWASAN KEUANGAN DAERAH, SUMBER DAYA MANUSIA, DAN PEMANFATAN TEKNOLOGI INFORMASI TERHADAP KETEPATWAKTUAN PELAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Empiris Pada SKPD Pemerintah Kabupaten Bantul) - muhamad azis anshori (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
The purpose of this study is to determine the influence of regional financial supervision, human resources and utilization of information technology to the timeliness of local government financial reporting. The data used in this study is the primary data obtained from the distribution of questionnaires to respondents. Population in this research is part of accounting / administration finance at SKPD in Bantul regency, the sample taken is 21 SKPD. Sampling technique using porposive sampling. The method of analysis used in this study is multiple linear regression analysis. The result of the research shows that the supervision of regional finance and the utilization of information technology has significant influence on the timeliness of local government financial reporting, while the human resource variable does not affect the timeliness of regional government financial reporting.